Komunikasi Spiritual Wanita Karir di Lingkungan Rumah Sakit Kota Bandung - Tri Nur Aini Noviar; Kiki Zakiah; Erik Setiawan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
This study explores the motives and meaning of recitation as a form of spiritual communication for career women in the Bandung city hospital environment. This study uses a qualitative approach with phenomenological methods, including interviews and observations. The study results show that the meaning of recitation as a form of spiritual communication as a means. The meaning of recitation as a form of spiritual communication as an activity. This meaning is driven by two kinds of motives, namely learning motives and needs motives. Learning explanations emphasize the desire to seek knowledge, share experiences and understand religious issues. Meanwhile, the need motive emphasizes encouragement from within and outside the individual, such as the desire to live a more balanced life between the life of the world and the hereafter, the need for friends or socialization. The motives and meanings possessed by key informants are not entirely separate but have overlaps so that the findings of this study cannot be categorized as a single motive. The motives owned by career women lead them to an understanding that recitation is a means and activity to return to their God Almight.